2004
DOI: 10.1158/1078-0432.ccr-02-1441
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Activated Akt Expression in Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: Akt is a serine/threonine kinase that plays a central role in tumorigenesis. Among the members of Akt family, Akt2 is associated with the development of human cancers. The present study was designed to clarify the prognostic significance of Akt2 and activated Akt expression in pancreatic ductal adenocarcinoma (PDAC). In addition, activated extracellular signal-regulated kinase 1 and 2 (ERK1/2) and the proliferation activity of tumor cells detected by Ki-67 immunohistochemistry were examined.Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(174 citation statements)
references
References 24 publications
16
153
3
2
Order By: Relevance
“…In particular, the reduction of phosphorylated Akt correlated with the enhancement of gemcitabine-induced apoptosis and antitumour activity, suggesting that the PI3K-Akt pathway plays a significant role in mediating drug resistance in several pancreatic cancer cells (Bondar et al, 2002). Moreover, an immunohistochemical analysis in patients who underwent curative resection revealed that p-Akt expression was a prognostic factor for overall survival in primary pancreatic adenocarcinoma (Yamamoto et al, 2004). Therefore, the inhibition of Akt might be a possible molecular target for novel therapeutic strategies and the present study demonstrated that pemetrexed significantly decreased the amount of the activated form of Akt.…”
Section: Discussionsupporting
confidence: 57%
“…In particular, the reduction of phosphorylated Akt correlated with the enhancement of gemcitabine-induced apoptosis and antitumour activity, suggesting that the PI3K-Akt pathway plays a significant role in mediating drug resistance in several pancreatic cancer cells (Bondar et al, 2002). Moreover, an immunohistochemical analysis in patients who underwent curative resection revealed that p-Akt expression was a prognostic factor for overall survival in primary pancreatic adenocarcinoma (Yamamoto et al, 2004). Therefore, the inhibition of Akt might be a possible molecular target for novel therapeutic strategies and the present study demonstrated that pemetrexed significantly decreased the amount of the activated form of Akt.…”
Section: Discussionsupporting
confidence: 57%
“…However, earlier studies of Akt expression in human cancers have yielded conflicting results. In pancreatic cancer, one study showed a correlation between higher p-Akt expression and shorter survival (Yamamoto et al, 2004), whereas another study showed the opposite (Chadha et al, 2006). Higher p-Akt expression was associated with poor outcomes in breast cancer (Zhou et al, 2004), and with lymph node metastasis or advanced disease stage in colorectal cancer (Itoh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Akt and its expression has been reported in pancreatic adenocarcinoma. Prognostic significance of activated Akt expression was reported in one study 153 that found that patients with low intensity p-Akt expression showed a significantly better 5-year survival rate than those with high expression, and univariate analysis revealed that p-Akt expression was significant in overall survival. Another study 154 found similar results, with expression of p-Akt correlating with survival both on univariate and multivariate analysis.…”
Section: Future Biomarkers In Pancreaticmentioning
confidence: 97%